Tetramethylammonium Hydroxide-doped Starch Film as a Colorimetric Sensor for Trinitrotoluene Detection - Wilasinee SRIPROM; Aree CHOODUM; Chanadda PHAWACHALOTORN; Worawit WONGNIRAMAIKUL; Wadcharawadee LIMSAKUL (My University, 2020)
A tetramethylammonium hydroxide (TMAH)-doped starch film was developed for trinitrotoluene (TNT) detection. A purple Janowsky anion was obtained from the reaction of TNT with released TMAH. When the film was used in conjunction with digital image colorimetry (DIC), rapid quantitative analysis of TNT was achieved. The Red-Green-Blue (RGB) intensities analyzed from digital photographs of the purple product were used to establish calibration curves for TNT. A wide linear range (2.5 to 50 mgL−1) with good linearity (R2 > 0.99) was achieved for the quantification of TNT. Good precision (1.73 to 3.74%RSD) was obtained for inter-day tests (n = 5). The films were applied to test four post-blast soil samples and two positive results were observed. The concentrations quantified by DIC were in good agreement with spectrophotometry. The film was able to be stored in a freezer for 3 months with <4.3% change in performance.
Keywords: Tetramethylammonium hydroxide; Trinitrotoluene; Colorimetry; Tetramethylammonium; Ammonium hydroxide; pH indicator; Crystal violet; Molecular Sensors and Ion Detection